Minimally Invasive Decompression Versus X-Stop in Lumbar Spinal Stenosis: A Randomized Controlled Multicenter Study. Issue 2 (15th January 2015) - Lønne, Greger; Johnsen, Lars Gunnar; Rossvoll, Ivar; Andresen, Hege; Storheim, Kjersti; Zwart, John Anker; Nygaard, Øystein P.
Abstract : Study Design: Prospective randomized controlled multicenter study. Objective: To compare the effect of X-Stop with minimally invasive decompression (MID) in patients with neurogenic intermittent claudication due to lumbar spinal stenosis. Summary of Background Data: Lumbar spinal stenosis is the most common indication for operative treatment in elderly. Laminectomy has been the "gold standard, " but MID is now widely used. Another minimally invasive surgery option is X-Stop showing good result compared with nonoperative treatment, but showing higher reoperation rate than laminectomy. Methods: We enrolled 96 patients aged 50 to 85 years, with symptoms of neurogenic intermittent claudication within 250-m walking distance and 1- or 2-level lumbar spinal stenosis, randomized to either MID or X-Stop. Primary outcome was Zurich Claudication Questionnaire in this intention-to-treat analysis. Secondary outcome was Oswestry Disability Index, EuroQol 5-dimensional questionnaire, numerical rating scale 11 for lower back pain and leg pain, and risk for secondary surgery and complications. Results: No significant differences were found in Zurich Claudication Questionnaire between the groups at any follow-ups. Both groups had a statistical and clinical significant improvement at 6 weeks and throughout the 2-year observation period. The number of patients having secondary surgery due to persistent or recurrent symptoms was significantly higher in the X-Stop group, odds ratio (95% confidence interval) = 6.5 (1.3–31.9). Complication rate was similar and low, but more severe for MID. Conclusion: Both MID and X-Stop led to significant symptom improvements. There were no significant clinical differences in effect between the methods at any of the follow-up time points. X-Stop had significant higher risk of secondary surgery. Complication was more severe for MID. Level of Evidence: 2 Abstract : This study compares the effect of X-Stop with minimally invasive decompression in patients with lumbar spinal stenosis. There was no difference in effect between the groups at follow-ups in the intention-to-treat analyses, but X-Stop had significant higher risk of secondary surgery. Complications were more severe for minimally invasive decompression.